Influence of workplace spirituality in the job satisfaction of the public sector employees - Oriol , Ettore de Carvalho (2022)
The spirituality of the human being is a subject discussed since ancient times. Until today, no civilization was finding that did not have some kind of developed religion and spirituality. Spirituality is finding in many ways and in many places, including in the workplace.  The objective of this research was to verify whether workplace spirituality influences job satisfaction of public sector employees. A survey based on a model created from the scales of workplace spirituality (Liu & Robertson, 2011) and job satisfaction (Siqueira, 2008) was conducted in a Brazilian public organization. Data analysis was done with SEM-CB. The results validate the model for predicting the influence of workplace spirituality on job satisfaction. We improved the model by providing context and by endorsing the idea that managers are able to improve the satisfaction of their work force, especially those working in the public sector, to deliver better services to citizens.